Tindakan Kekerasan terhadap Perempuan dalam Perspektif Sosio-Yuridis - Harkrisnowo, Harkristuti (Jurnal Hukum IUS QUIA IUSTUM, 2016)
As aform of crime, Durkheim’s opinion, the woman violence as well as other forms of crime seems continuously to appear In this world. However, it does not mean that the frecuency, prevalence, and incidence of the women violence cannot be declined. To overcome this problem, both the juridical attempt and awareness of societies are necessary to conduct Without public participation, the violence is Impossible to be to change the societies "behavior and attitude, the policy makers -from the highest to the lowest level especially those who have discretionary power- are very important.